Radiomic features from the peritumoral brain parenchyma on treatment-naïve multi-parametric MR imaging predict long versus short-term survival in Glioblastoma Multiforme: Preliminary Findings - Prasanna, Prateek (Eur Radiol, 2016)
OBJECTIVE: Despite 90% Glioblastoma (GBM) recurrences occurring in the peritumoral brain zone (PBZ), its contribution in patient survival is poorly understood. The current study leverages computerized texture (i.e. radiomic) analysis to evaluate the efficacy of PBZ features from preoperative MRI in predicting long (>18-months) versus short-term (<7-months) survival in GBM. METHODS: 65 patient exams (29 short-term, 36 long-term) with Gadolinium-contrast T(1w), FLAIR, T(2w) sequences from the Cancer Imaging Archive were employed. An expert manually segmented each study as: enhancing lesion, PBZ, and tumour necrosis. 402 radiomic features (capturing co-occurrence, gray-level dependence, directional gradients) was obtained for each region. Evaluation was performed using 3-fold cross validation, such that a subset of studies was used to select the most predictive features, and the remaining subset was used to evaluate their efficacy in predicting survival. RESULTS: A subset of 10 radiomic “peritumoral” MRI features, suggestive of intensity heterogeneity and textural patterns, was found to be predictive of survival (p = 1.47 × 10(−5)), as compared to features from enhancing tumour, necrotic regions, and known clinical factors. CONCLUSION: Our preliminary analysis suggests that radiomic features from the PBZ on routine pre-operative MRI may be predictive of long-, versus short-term survival in GBM.